2020
DOI: 10.1038/s41467-020-18611-5
|View full text |Cite
|
Sign up to set email alerts
|

Massive and rapid COVID-19 testing is feasible by extraction-free SARS-CoV-2 RT-PCR

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is commonly diagnosed by reverse transcription polymerase chain reaction (RT-PCR) to detect viral RNA in patient samples, but RNA extraction constitutes a major bottleneck in current testing. Methodological simplification could increase diagnostic availability and efficiency, benefitting patient care and infection control. Here, we describe methods circumventing RNA extraction in COVID-19 testing by per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
431
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(455 citation statements)
references
References 14 publications
(15 reference statements)
20
431
2
2
Order By: Relevance
“…This dilution seems to provide the optimum balance between input RNA and reducing the concentrations of PCR inhibitors. A similar observation was found by Smyrlaki et al [ 12 ] where they reported that dilution of the clinical samples is essential to dilute the inhibitors that might be present in the samples. Heating the diluted specimen to 95 °C followed by quenching at 4 °C for 5 min was used to deactivate possible PCR inhibitors that might be present in the samples and to denature viral proteins.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This dilution seems to provide the optimum balance between input RNA and reducing the concentrations of PCR inhibitors. A similar observation was found by Smyrlaki et al [ 12 ] where they reported that dilution of the clinical samples is essential to dilute the inhibitors that might be present in the samples. Heating the diluted specimen to 95 °C followed by quenching at 4 °C for 5 min was used to deactivate possible PCR inhibitors that might be present in the samples and to denature viral proteins.…”
Section: Discussionsupporting
confidence: 82%
“…While the 5 min denaturation provided a comparable LoD to the standard protocol, the 10-min denaturation resulted in much higher Ct values, possibly due to viral RNA degradation. Heating at 95 °C was reported by Smyrlski et al [ 12 ] to help inactivate the nucleases and inhibitors in the clinical samples and was most importantly found to inactivate SARS-coV-2. Bruce et al [ 11 ] also showed that heating is important for the detection of low viral load samples most probably since it denatured RNases/inhibitors of the enzymes and/or improved the accessibility of viral RNA through direct lysis of cells and virions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported LOD for detecting SARS-CoV-2, evaluated using SARS-CoV-2 positive saliva, was 6,000 virus 90 copies per ml of saliva. In direct RT-PCR tests, addition of non-ionic detergents, such as Tween-20 and Triton X-100, to saliva or swab-derived samples was shown to increase the sensitivity of SARS-CoV-2 RNA detection [7,11].…”
mentioning
confidence: 99%
“…[16][17][18] Furthermore, these drive-through tests are available only for preregistered and eligible patients with access to automobiles. As rapid and affordable tests for COVID-19 are showing promise, 19 the USPS facilities and workforce could be leveraged to broaden access, especially for these underserved groups. With more than 600,000 workers, facilities in every county, and in more than 28,000 of the approximately 33,000 ZIP Code Tabulation Areas (ZCTAs) in the United States, USPS has a nationwide presence (ZCTAs are generalized areal representations of ZIP codes used by the US Census Bureau 20 ).…”
mentioning
confidence: 99%